The Inherent Link between Gender and Sexuality: A Queer View to the Portrayal of Women in Herland, Things Fall Apart, Bombay Brides, and The Winner Stands Alone - Roy, Suparna (Salasika, 2021)
Stevie Jackson and Jackie Jones regarded in her article- Contemporary Feminist Theory that “The concepts of gender and sexuality as a highly ambiguous term, as a point of reference” (Jackson, 131, ch-10). Gender and Sexuality are two most complexly designed, culturally constructed and ambiguously interrelated terms used within the spectrum of Feminism that considers “sex” as an operative term to theorize its deconstructive cultural perspectives. Helene Cixous notes in Laugh of Medusa that men and women enter the symbolic order in a different way and the subject position open to either sex is different. Cixious’s understanding that the centre of the symbolic order is ‘phallus’ and everybody surrounding it stands in the periphery makes women (without intersectionality) as the victim of this phallocentric society. One needs to stop thinking Gender as inherently linked to one’s sex and that it is natural. To say, nothing is natural. The body is just a word (as Judith Butler said in her book Gender Trouble [1990]) that is strategically used under artificial rules for the convenience of ‘power’ to operate. It has been a “norm” to connect one’s sexuality with their Gender and establish that as “naturally built”. The dichotomy of ‘penis/vagina’ over years has linked itself to make/female understanding of bodies. Therefore my main argument in this paper is to draw few instances from some literary works which over time reflected how the gender- female/women characters are made to couple up with a male/man presenting the inherent, coherent compulsory relation between one’s gender and sexuality obliterating any possibility of ‘queer’ relationships, includes- Charlotte Perkins Gilman’s Herland (1915), Bombay Brides (2018) by Esther David, Paulo Coelho’s Winner Stands Alone (2008) and Chinua Achebe’s Things Fall apart (1958).